Preventing Money Politics: Bawaslu Role in Batu City Regional Head Election - Muhammad Wahyu Prasetyo Adi, Muhammad Wahyu Prasetyo Adi (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2025)
The practice of money politics in Batu City is an old symptom that is still rooted in the political year. Like the 2017 political year, money politics is incarnated in the packaging of goods, from basic necessities to clothing. This is also evident in other political events, such as in 2019 and 2024. The purpose of this research is to analyze Bawaslu's role in preventing money politics in the 2024 political year with a focus on digital media campaigns and community-based education. Through a qualitative approach with a descriptive type, this research focuses on selecting informants by purposive sampling. Using primary and secondary data collection techniques, this study selected informants who have the capacity and understanding of Bawaslu's role in understanding local dynamics with the prevention role theory. The first result is through the digitization of information, namely using Instagram and the official website as a visualization of election material, criminal threats for those who deviate from the appeal to carry out the correct voting process. In this context, the main target is mass media users who do not limit their age. Second, through political education in each village, this orientation is due to the topography of Batu City, where the majority of villages and the 2017 political year is a track record of money politics in the village so that the vulnerability of money politics must be based on its potential. The implications of this research understand Bawaslu's strategy in preventing money politics in the 2024 Regional Head Election.